The aquatic carnivorous plant Aldrovanda vesiculosa (Droseraceae) exhibits altered developmental stages in male gametophyte - Onelli, Elisabetta; Beretta, Mario; Moscatelli, Alessandra; Caccianiga, Marco; Pozzi, Michele; Stroppa, Nadia; Adamec, Lubomír (Protoplasma, 2021)
Aldrovanda vesiculosa (Droseraceae) is a rare aquatic carnivorous plant, distributed in Europe, Asia, Africa, and Australia. Aldrovanda populations can flower prolifically under favourable conditions, but seed set is very limited. We studied the structure of Aldrovanda pollen collected from flowers in different developmental stages (opened and non-opened anthers) from both European and Australian populations to elucidate pollination traits and the basis of poor seed set on the basis of microscopic observation of pollen and anther structure. Microscopic analyses of Aldrovanda pollen showed that this plant has pollen arranged in tetrads like other species in the Droseraceae family. In hydrated pollen, cytoplasmic protrusions originate from pores located along the equatorial wall of monads, and can develop into pollen tubes. Interestingly, pollen development from microspores occurs in open anthers, suggesting a delay of the developmental stages. In addition, pollen development displays altered sperm cell formation and precocious pollen germination. Precocious germination may characterize recalcitrant pollen, which naturally do not undergo dehydration before anthesis and remain partially hydrated, particularly in aquatic and wetland plants. These alterations of male gametophyte development could affect fertilization processes, and be the reason for the low reproductive capability of Aldrovanda observed both in the field and in cultures. Generally, reduced pollen longevity and very quick germination are considered an adaptation to aquatic or wet environments.
Keywords: Aldrovanda vesiculosa; Pollination; Carnivorous Plant; pyl; masožravé rostliny; Pollen development; Pollen structure; Anther structure; zárodečné buňky rostlin; Pollen; Generative cell; Germ Cells, Plant; Droseraceae